Pengaruh Inventory Intensity, Kepemilikan Institusional, Deferred Tax Expense, dan Dewan Komisaris Independen terhadap Tax Avoidance - Shilvya Miranda; Endah Finatariani (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to analyze the impact of Inventory Intensity, Institutional Ownership, Deferred Tax Expense, and Independent Board of Commissioners on Tax Avoidance in consumer noncyclicals companies listed on the Indonesia Stock Exchange during the period 2019-2023. The data used is secondary data with a total population of 126 companies per year. The sample was selected using purposive sampling, and after removing 16 companies detected as outliers, 50 companies were selected as the sample over a five-year period. The analysis was conducted using multiple linear regression with Eviews software version 12, applying a panel data model with a Common Effect model. The findings show that all variables simultaneously have a significant impact on Tax Avoidance. However, partially, only Inventory Intensity and Deferred Tax Expense have a significant effect on Tax Avoidance, while Institutional Ownership and Independent Board of Commissioners do not show any significant impact on Tax Avoidance. This research provides insights into the factors influencing tax avoidance in Indonesian listed companies.